Targeted management of evolving and established chronic lung disease of prematurity assisted by cardiopulmonary ultrasound: A case report of four patients - Bruno, Guglielmo; Chioma, Roberto; Storti, Enrico; De Luca, Giovanni; Fantinato, Margherita; Antonazzo, Patrizio; Pierro, Maria (Frontiers in Pediatrics, 2023)
Bronchopulmonary dysplasia (BPD) is one of the most common complications of premature birth. The current definition of BPD is based on the duration of oxygen therapy and/or respiratory support. Among the pitfalls of all the diagnostic definitions, the lack of a proper pathophysiologic classification makes it difficult to choose an appropriate drug strategy for BPD. In this case report, we describe the clinical course of four premature infants, admitted to the neonatal intensive care unit, for whom the use of lung and cardiac ultrasound was an integral part of the diagnostic and therapeutic process. We describe, for the first time to our knowledge, four different cardiopulmonary ultrasound patterns of evolving and established chronic lung disease of prematurity and the consequent therapeutic choices. This approach, if confirmed in prospective studies, may guide the personalized management of infants suffering from evolving and established BPD, optimizing the chances of success of the therapies and at the same time reducing the risk of exposure to inadequate and potentially harmful drugs.